The Board Structure and Dividend Payout Policy: Empirical Evidence from BIST 100, Turkey - Saliya, Abdela Yasin; Dogukanli, Hatice (Asian Journal of Economic Modelling, 2022)
There are various theories regarding the secret of dividend preference over other alternatives. The most notable of these dividend theories is the agency theory. Dividends play a vital role in mitigating agency costs between shareholders and managers. This study is distinct from others since it includes more separate board structure variables with long study periods using a panel econometric model. Hence, the present study aims to investigate the links between board attributes and dividends payout policy of listed industrial companies of Turkey from 2011 to 2019. Data were collected from the sampled companies that were listed on the Borsa Istanbul BIST 100 indexes as of December 31, 2019, from Finnet (data provider). The study employed the panel Tobit model and found a significant positive effect of board size on dividend payout policy and a significant negative impact of board meeting frequency on the payout policy of listed companies in Turkey.